Radio revista sobre el uso del tiempo libre de los jóvenes de Cayambe. - Amán Luje, Lady Carolina (2016)
This research proposes a radio program for young people of Cayambe, whose main objective is to generate a edu-communicative and radio tool that encourages the proper use of free time, through a serial recording containing ten radio programs. The communicative product began its development with previous research that contributed in the acquisition of information, then the methodological techniques were applied; surveys and interviews, which were used as reference for the design of scripts and radio scripts. In addition, the results of surveys to students between 14 and 18, which define and determine the use of free time in youth people of Cayambe, these data were used to create this edu-communicative space presenting information on topics of interest to young people. Finally, through an assessment shows that the radio serial magazine has made acceptance of said target.